Edible film: A future thrust in packaging technology for horticultural crops - Ffadhilah, A; Chitra, R; Ganga, M; Prasanthrajan, M; Djanaguiraman, M (Plant Science Today, 2024)
The significance of edible film in food packaging is increasingly recognized, especially in preserving perishable items such as fruits and vegetables. Packaging serves crucial functions, including containment, protection and facilitation of product transportation. However, conventional plastic packaging poses significant environmental challenges due to its non-biodegradable nature, contributing to pollution and heightened carbon footprints. In contrast, edible films, derived from natural ingredients like proteins, lipids and polysaccharides, offer a sustainable alternative. These films extend the shelf life of food products and improve food quality by reducing waste and minimizing environmental impact. Adopting edible films in the horticultural sector could significantly enhance post-harvest preservation, ensuring the freshness and quality of produce. As the food industry evolves, the development and application of edible film packaging present a promising avenue for future research, emphasizing sustainability and efficiency in food preservation.